Mindful Parenting Training to Reduce Parenting Stress in Mothers of Children with Severe Non-Verbal Autism - Latifa, Indah Nur; Sansani, Ries; Oktavia, Citrawanti (World Psychology, 2025)
This study was intended to assess the effectiveness of mindful parenting training in reducing the level of parenting stress in mothers who have children with non-verbal Autism Spectrum Disorder (ASD). The research design used was Single Case Experimental Design (SCED) with A-B-A approach, involving three mothers as participants. Intervention in the form of mindful parenting training that integrates increased knowledge of yoga concepts and skills was conducted over several sessions. Data were collected through Parental Stress Scale (PSS) instrument, mindful parenting concept knowledge test, and yoga skill observation. Data were analyzed by descriptive statistics and visual graph analysis. Results showed an increase in scores on aspects of mindful parenting knowledge and skills, accompanied by a decrease in the average parenting stress score from 29.33 to 28.00. Although this decrease was moderate quantitatively, the general pattern showed that two out of three participants experienced a consistent decrease in stress. These findings indicate that mindful parenting training has the potential to improve mothers' cognitive capacity and emotion regulation, and is functionally relevant in supporting the parenting of non-verbal ASD children